Environmentally conscious schools through the implementation of Adiwiyata program at junior high schools in Jakarta - Nursofah, Nursofah; Sari, Eliana; Supadi, Supadi (Edelweiss Applied Science and Technology, 2025)
Environmental problems such as littering, excessive use of single-use plastics, and low participation in greening activities are still widely found in the school environment, indicating the need for more systematic and sustainable awareness-raising efforts. This study aims to evaluate the implementation of the Adiwiyata program in junior high schools in Jakarta. The research used a qualitative approach with an evaluative design of the CIPP (Context, Input, Process, Product) model. The research data were collected through in-depth interviews, observation, and documentation, involving principals, teachers, and students. The results showed that the effectiveness of the program was strongly influenced by leadership commitment, participation of all school members, and continuous evaluation practices. Context analysis showed alignment between national environmental policies and school needs. Input analysis found key resources and strategies, while process analysis highlighted collaborative implementation. Product analysis showed positive changes in students’ environmentally friendly attitudes and behaviors. This study concludes that the Adiwiyata program contributes significantly to shaping environmental values and habits in schools. The practical implication is that schools that want to develop environmental education should encourage inclusive engagement and implement a structured evaluation system. The results of this study can serve as a reference for schools that want to develop environmental education.